Accuracy of classification of invasive lobular carcinoma on needle core biopsy of the breast. Issue 12 (10th August 2016) - Naidoo, Kalnisha; Beardsley, Brooke; Carder, Pauline J; Deb, Rahul; Fish, David; Girling, Anne; Hales, Sally; Howe, Miles; Wastall, Laura M; Lane, Sally; Lee, Andrew H S; Philippidou, Marianna; et al.
Abstract : Although the UK National Institute for Health and Care Excellence guidelines recommend that in patients with biopsy-proven invasive lobular carcinoma (ILC), preoperative MRI scan is considered, the accuracy of diagnosis of ILC in core biopsy of the breast has not been previously investigated. Eleven pathology laboratories from the UK and Ireland submitted data on 1112 cases interpreted as showing features of ILC, or mixed ILC and IDC/no special type (NST)/other tumour type, on needle core biopsy through retrieval of histology reports. Of the total 1112 cases, 844 were shown to be pure ILC on surgical excision, 154 were mixed ILC plus another type (invariably ductal/NST) and 113 were shown to be ductal/NST. Of those lesions categorised as pure ILC on core, 93% had an element of ILC correctly identified in the core biopsy sample and could be considered concordant. Of cores diagnosed as mixed ILC plus another type on core, complete agreement between core and excision was 46%, with 27% cases of pure ILC, whilst 26% non-concordant. These data indicate that there is not a large excess of expensive MRIs being performed as a result of miscategorisation histologically.